Band alignment and charge transfer pathway in three phase anatase-rutile-brookite TiO2 nanotubes: an efficient photocatalyst for water splitting - Preethi, L. K.; Mathews, Tom; Nand, Mangla; Jha, S. N.; Chinnakonda, Gopinath S.; Dash, Sitaram (Applied Catalysis B-Environmental, 2017)
The study reports electrochemical synthesis, phase evolution and hydrogen generation efficiency of anatase, anatase-rutile and anatase-rutile-brookite (ARB) TiO2 nanotubes for the first time. The SEM and TEM micrographs confirm the tubular morphology of the samples. The presence of anatase, rutile and brookite phases in a single nanotube is confirmed from high resolution TEM analysis. The water splitting efficiency of the three systems are studied under one sun illumination. It is observed that the anatase-rutile-brookite TiO2 nanotubes are highly efficient compared to anatase-rutile or anatase TiO2 nanotubes. The hydrogen generated by ARB composites, after four hours of one sun illumination, is found to be nearly twice that of anatase TiO2 nanotubes and 1.6 times that of anatase-rutile TiO2 nanotubes. The results suggest that the ARB in single nanotube having two junction interfaces, highly facilitate interparticle charge transfer compared to single junction anatase-rutile or bare anatase TiO2 nanotubes. From the deconvolution of PL spectra and the synchrotron radiation assisted valence band edge analysis, the band diagram for the anatase-rutile-brookite phase is constructed. The charge separation and its transfer pathway for efficient photo-assisted water splitting are delineated. This opens a new route for the simple synthesis and study of tri-phase TiO2 for efficient photocatalytic water splitting compared to the widely studied two phase TiO2. (C) 2017 Published by Elsevier B.V.
Keywords: Anatase-Rutile-Brookite; Hydrogen generation; nanotubes; Photocatalysis; photoluminescence; Valence band edge

Study on doped heterojunctions in TiO2 nanotubes: an efficient photocatalyst for solar water splitting - Preethi, L. K.; Antony, Rajini P.; Mathews, Tom; Walczak, Lukasz; Gopinath, Chinnakonda S. (Scientific Reports, 2017)
The two important factors that affect sunlight assisted water splitting ability of TiO2 are its charge recombination and large band gap. We report the first demonstration of nitrogen doped triphase (anatase-rutile-brookite) TiO2 nanotubes as sun light active photocatalyst for water splitting with high quantum efficiency. Nitrogen doped triphase TiO2 nanotubes, corresponding to different nitrogen concentrations, are synthesized electrochemically. Increase in nitrogen concentration in triphase TiO2 nanotubes is found to induce brookite to anatase phase transformation. The variation in density of intra-band states (Ti3+ and N 2p states) with increase in nitrogen doping are found to be critical in tuning the photocatalytic activity of TiO2 nanotubes. The presence of bulk heterojunctions in single nanotube of different nitrogen doped TiO2 samples is confirmed from HRTEM analysis. The most active nitrogen doped triphase TiO2 nanotubes are found to be 12 times efficient compared to pristine triphase TiO2, for solar hydrogen generation. The band alignment and charge transfer pathways in nitrogen doped TiO2 with triphase heterojunctions are delineated. Bulk heterojunctions among the three phases present in the nanotubes with intra-band defect states is shown to enhance the photocatalytic activity tremendously. Our study also confirms the theory that three phase system is efficient in photocatalysis compared to two phase system.

Marginally hydrogenated triphasic titania nanotubes for effective visible-light photocatalytic hydrogen generation - Preethi, Laguduva K.; Mathews, Tom; Walczak, Lukasz; Gopinath, Chinnakonda S. (Energy Technology, 2018)
We report the first demonstration of hydrogen-annealed triphase TiO nanotubes (anatase-rutile-brookite) (T-ARB) as a visible-light-active photocatalyst for water splitting with high quantum efficiency. As-synthesized T-ARB was annealed under hydrogen atmosphere at 250 and 4508 degrees C for 2 h. We found that the tubular structures were retained in the hydrogenated TiO2 samples. It was observed that the concentrations of Ti3+ and the oxygen vacancies and their distribution significantly increased with respect to the hydrogen annealing temperature. Such changes in defects were found to be critical in enhancing the photocatalytic activity of the hydrogen-annealed triphase TiO2 nanotubes. The triphase TiO2 nanotubes hydrogen annealed at 450 degrees C were 16 times more efficient than pristine TiO2. Such an increase in the photocatalytic activity was explained by a triphase band diagram with defect states below the conduction band of each phase, which facilitated visible-light activity and easy transfer of charge carriers from one phase to another. Our study showed that the well-designed multiphase construction with oxygen vacancies enhanced the photocatalytic activity tremendously owing to the presence of a higher number of phase junctions.
Keywords: charge transfer; Defects; Hydrogenation; titania; water splitting